2002
DOI: 10.1029/2002gl015480
|View full text |Cite
|
Sign up to set email alerts
|

Si and O diffusion in olivine and implications for characterizing plastic flow in the mantle

Abstract: [1] The relationship between diffusion of individual species and creep of silicates is unclear and has long been debated, factually anchored by the central observation that the activation energies for creep are higher than the activation energy for diffusion of any species. There have been numerous attempts to explain this difference. New advances in experimental technology enable us to demonstrate that this difference does not exist and was an artefact of the limited experimental resolution of earlier studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
130
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(141 citation statements)
references
References 23 publications
9
130
2
Order By: Relevance
“…The various studies yield a fairly consistent range for activation enthalpy of about 240 to 355 kJ mol −1 that may however be extended due to experimental uncertainties. These values are markedly lower than the value for diffusion of Si in olivine of 530 kJ mol −1 (Dohmen et al, 2002), relevant if dislocation climb was rate-controlling for the recovery processes (Karato et al, 1993). The requirement expressed by Eq.…”
Section: Quantitative Analysismentioning
confidence: 66%
“…The various studies yield a fairly consistent range for activation enthalpy of about 240 to 355 kJ mol −1 that may however be extended due to experimental uncertainties. These values are markedly lower than the value for diffusion of Si in olivine of 530 kJ mol −1 (Dohmen et al, 2002), relevant if dislocation climb was rate-controlling for the recovery processes (Karato et al, 1993). The requirement expressed by Eq.…”
Section: Quantitative Analysismentioning
confidence: 66%
“…(1) Si is the rate-controlling species in wadsleyite and controls the plastic deformation. Although there is a lack of oxygen diffusion data for wadsleyite, Si is a good candidate for the slowest diffusion species in wadsleyite, as it is in olivine [Houlier et al, 1988;Dohmen et al, 2002].…”
Section: Discussionmentioning
confidence: 99%
“…[3] There are numerous studies on diffusivity in olivine, which have shown that Si is the slowest diffusing species [e.g., Houlier et al, 1988Houlier et al, , 1990Dohmen et al, 2002]. However diffusion studies in wadsleyite, a high-pressure polymorph of olivine and one of the major constituent minerals in the mantle transition zone, have been limited to Mg-Fe interdiffusion [Farber et al, 1994[Farber et al, , 2000Chakraborty et al, 1999;Kubo et al, 2004].…”
Section: Introductionmentioning
confidence: 99%
“…Since the diffusion coefficient is obtained for a temperature range of 1100 Dohmen et al 2002), we extrapolate the results down to lower temperatures. Measurements with the transmission electron microscope show that the chemical compositions of presolar silicate grains vary on the scale of a few tens nanometer (Nguyen et al 2007;Busemann et al 2009;Leitner et al 2012).…”
Section: Isotopic Diffusion In Thermally Evolving Planetesimalsmentioning
confidence: 99%
“…In order to compute the diffusion length of oxygen isotopes in presolar silicate grains, we adopt a diffusion coefficient of 18 O in olivine from Dohmen et al (2002). The diffusion coefficient D(T ) is given as…”
Section: Isotopic Diffusion In Thermally Evolving Planetesimalsmentioning
confidence: 99%